Decision Support System For The Best Student Selection Recommendation Using Ahp (Analytic Hierarchy Process) Method - Dona Katarina; Aji Nurrohman; Wibisono; Priatno; Arman Syah Putra (International Journal of Educational Research & Social Sciences, 2021)
The background of this research is how to choose the best students in school using the AHP algorithm. Then it can be determined who the best students are. Based on the system that will be input and processed by the system so that it will produce maximum output and not in favor of anyone. The method used in this study is to use the literature study method. And literature study using these 2 methods will be able to provide something new, especially in the field of problem formulation and novel poles will be found after that the method is to conduct trials by inputting process and output so that you can find out who the best students in school. The problem raised in this study is how to determine the best students. Based on the system not based on the choice of someone with the system, it will help the school in determining the best students so that it does not side with one party and choose the wrong choice. In this study will produce data that can be known which students will be selected to be the best students in school based on the process of the AHP algorithm that has been included in this study.